Sunlight-thin nanophotonic monocrystalline silicon solar cells. Issue 2 (30th August 2017) - Depauw, Valérie; Trompoukis, Christos; Massiot, Inès; Chen, Wanghua; Dmitriev, Alexandre; Cabarrocas, Pere Roca i; Gordon, Ivan; Poortmans, Jef
Abstract: Introducing nanophotonics into photovoltaics sets the path for scaling down the surface texture of crystalline-silicon solar cells from the micro- to the nanoscale, allowing to further boost the photon absorption while reducing silicon material loss. However, keeping excellent electrical performance has proven to be very challenging, as the absorber is damaged by the nanotexturing and the sensitivity to the surface recombination is dramatically increased. Here we realize a light-wavelength-scale nanotextured monocrystalline silicon cell with the confirmed efficiency of 8.6% and an effective thickness of only 830 nm. For this we adopt a self-assembled large-area and industry-compatible amorphous ordered nanopatterning, combined with an advanced surface passivation, earning strongly enhanced solar light absorption while retaining efficient electron collection. This prompts the development of highly efficient flexible and semitransparent photovoltaics, based on the industrially mature monocrystalline silicon technology.